Addressing the Opioid Crisis: A Dynamic Case-Based Module Set for Interprofessional Educators, Learners, and Clinicians - Rachel Porter; Jacqueline Barnett; Melinda Blazar; Sandro Pinheiro; Lynn Bowlby (Association of American Medical Colleges, 2022)
Introduction In 2017, the opioid crisis was declared a public health emergency in the United States. The CDC has called for a multifaceted, collaborative approach to address the opioid epidemic. Though many resources have been made available for provider education, much of what has been published to date has focused narrowly on specific contexts and/or has become outdated. Methods To address the need for more up-to-date and broad-based training, we designed a dynamic, module-based curriculum aligned with the 2016 CDC Opioid Prescribing Guideline. The three-part module set addresses safe opioid prescribing, recognizing and treating opioid use disorders, and opioids and pain management. Each module contains interactive content and assessments and culminates in case-based applications. The modules provide an anchor point for supplemental activities that can be utilized in various contexts. Results As of May 2021, we recorded 3,529 module completions (≥80% performance on module assessments). A 6-month follow-up survey revealed that the majority of respondents had used the strategies they had learned to improve their prescribing practice and believed they had improved outcomes for patients. Discussion The modules and supplementary resources can be used by clinicians and educators to combat the opioid epidemic with best practices in patient care and by meeting many state licensure requirements. Included supplemental resources are ideal for learners, providing a comprehensive understanding of the opioid crisis as well as tools for medication-assisted treatment that create capacity to immediately address these issues once learners become fully licensed.